Garden revolution : how our landscapes can be a source of environmental change - Weaner, Larry; Christopher, Thomas (Timber Press, 2016)
Garden Revolution shows how an ecological approach to planting can lead to beautiful gardens that buck much of conventional gardening's counter-productive, time-consuming practices. Instead of picking the wrong plant and then constantly tilling, weeding, irrigating, and fertilizing, Larry Weaner advocates for choosing plants that are adapted to the soil and climate of a specific site and letting them naturally evolve over time.